The family is okay, thank you. It is on TV (Journal of Parents and Teachers, 2014)
This article presents the growing success of the TV series about very different kind of families: rich, poor, sophisticated, ordinary, traveling, conflictive or funny families. Family life is complex, surprising, and it is full of adventures. This explains the triumph of this type of TV series.
Keywords: TV series; families.